(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the theoretical foundations of retail services provided by commercial banks. It explores the concept of retail banking services, their structure, core characteristics, and their role in a market economy. The author examines various definitions and approaches found in economic literature and proposes a comprehensive theoretical framework. The theoretical insights presented in the article can serve as a basis for developing practical recommendations aimed at further developing the retail segment of banking services.